Yellow Bird : oil, murder, and a woman's search for justice in Indian country - Murdoch, Sierra Crane (Random House, 2020)
"When Lissa Yellow Bird was released from prison in 2009, she found her home, the Fort Berthold Indian Reservation in North Dakota, transformed by the Bakken oil boom. In her absence, the landscape had been altered beyond recognition, her tribal government swayed by corporate interests, and her community burdened by a surge in violence and addiction. Three years later, when Lissa learned that a young white oil worker, Kristopher 'KC' Clarke, had disappeared from his reservation worksite, she became particularly concerned. No one knew where Clarke had gone, and no one but his mother was actively looking for him. Unfolding like a gritty mystery, Yellow Bird traces Lissa's steps as she obsessively hunts for clues to Clarke's disappearance. She navigates two worlds -- that of her own tribe, changed by its newfound wealth, and that of the non-Native oil workers, down on their luck, who have come to find work on the heels of the economic recession. Her pursuit becomes an effort at redemption -- an atonement for her own crimes and a reckoning with generations of trauma. Yellow Bird is both an exquisitely written, masterfully reported story about a search for justice and a remarkable portrait of a complex woman who is smart, funny, eloquent, compassionate, and -- when it serves her cause -- manipulative. Ultimately, it is a deep examination of the legacy of systematic violence inflicted on a tribal nation and a tale of extraordinary healing"--